ASPECTS OF ROCK PROPERTIES ON UNCONFINED COMPRESSIVE STRENGTH FOR RESERVOIR IN BORNEO FIELD, LOWER KUTAI BASIN, EAST KALIMANTAN - Putu Satwika Wirawan, Gde
28-10aN is one of reservoirs in well XYZ that occupies deep zone interval between marker R28 and R28-2. Deep zone is one of six zones in Borneo field where has been producing gas (gas pool). This reservoir has very low porosity from 5.6 to 9.3%. Unconfined compressive strength (UCS) of 28-10aN is hypothized to be effected by grain size and porosity as significant attention in geomechanical testing, the effects of cementation, mineralogy, lithic fragments and clay matrix are not. Since the availability of data for geomechanical study is statistically very limited, then literature study and to have the use of models from the formers are important to prove the hypothesis. The data that have been used from UCS and considering a number of petrographic properties, such as thin section, scanning electron microscopy (SEM) and X-ray diffraction (XRD) which could influence the mechanical behavior of reservoir 28-10aN. This research shows that the variations of UCS of 28-10aN have not been only effected by grain size and porosity but cementation of quartz overgrowth, amount of silica/quartz, type of lithic fragments and clay matrix which predominate in reservoir. While, the type and the amount of carbonate cements in this case are less effective in controlling the strength of the reservoir.